Deficiencies of fibrillin and decorin in fibroblast cultures of a patient with neonatal Marfan syndrome. Issue 12 (December 1992) - Superti-Furga, A; Raghunath, M; Willems, P J
Abstract : Changes in the structure and metabolism of fibrillin, a microfibril associated protein, can result in classical Marfan syndrome, and reduced expression of decorin, a small extracellular chondroitin sulphate/dermatan sulphate proteoglycan, has been observed in fibroblasts of a patient with neonatally lethal Marfan syndrome. We have studied the synthesis of fibrillin and decorin in cultured fibroblasts of a further sporadic patient with neonatally lethal Marfan syndrome. Fibrillin immunoreactivity in the extracellular matrix of the patient's fibroblasts was markedly reduced, and the fibrillar pattern was absent, in spite of normal amounts of fibrillin mRNA. Decorin mRNA, synthesis, and immunoreactivity in the matrix were also reduced. The results indicate involvement of both fibrillin and decorin in the pathogenesis of neonatal Marfan syndrome in this patient, but do not indicate which is the primary defect. We speculate, however, that a structural defect of fibrillin leads to diminished incorporation of the protein into the extracellular matrix, and that underexpression of decorin is secondary to the primary fibrillin defect. Combined deficiency of fibrillin and decorin may be the cause of the severe clinical phenotype.